Interpersonal Relation: Sunda Wiwitan's Perception on Environment - UYUN, YUYUN WARDATUL ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Keywords: Sunda Wiwitan, environment, indigenous religion, world view, nature. Addressing the indigenous religion and the environment, there must be an assumption that they have a strong relationship each other. I believe that it cannot be separated from their world view, especially in seeing the self, the other selves and the relation between them. In this case, Rachelle A. Dickie (2005) affirms that people of indigenous religion perceive that people belong to the land, the natural surroundings, not the land belongs to the people. Likewise when talking about indigenous people of Sunda Wiwitan in Cigugur, in which they live in excellent harmony with the nature and surrounding, the question is: how do Sunda Wiwitan people define their relationship with environment? Do they consider nature as "person"? It still remains as a puzzle because we notice that due to the strong influence of globalization they may define nature as an object that can be exploited blindly. Then, to what extent do the ritual practice and belief for Sunda Wiwitan people in Cigugur in affecting the behavior towards environment? And what challenges encountered so far? Is there any different paradigm against the traditional paradigm of Sunda Wiwitan? Based on these questions, I want to reveal people of Sunda Wiwitan, (a) in relation to their world view on the self, the other selves and their relation, (b) the ritual of Seren Taun conducted which affects their behavior in the everyday life in maintaining the environmental surrounding also (c) the politicization of environment regarding to the challenge exists. This research, thus, aims at analyzing how Sunda Wiwitan people define the relationship with the environment as well as how their local wisdoms encourage the preservation of environment, by looking at their world view based on the theoretical framework built by Hallowel. In addition, it also aims at explaining how the ritual practice of Seren Taun held by Sunda Wiwitan people in Cigugur contribute positively to the environment and become an important base to change their attitude towards the environment as well as to reveal the challenge encountered by people of Sunda Wiwitan so far. This thesis included in the type of field research with the technique of descriptive analysis by applying the data collection in qualitative way i.e. by participant observation, semi-structured interviews and library research. Those methodologies will surely help me to obtain the insider perspective on how people of Sunda Wiwitan perceive the nature, the ritual practices and the challenges encountered so far. For the library research for example, the resources will provide many examples of narratives about the teaching and the views of Sunda Wiwitan community towards the environment and nature. The finding of this research shows that (1) Sunda Wiwitan people recognize animals, plants, the natural surrounding such as sun, moon, star, and even "objects" as persons. However they believe there are two qualities of the other-than-human person based on their role in giving the power to the surrounding. They are the other-than-human person with their passive power and the other-than-human person with the active power. It is then a little bit different from the Ojibwa people, says Hallowell, do not perceive stones, in general, as animate (1960). For people of Ojibwa the animate qualities quite determine whether something considered being other-than-human persons or not. While in Sunda Wiwitan they are considered person in general and have the capacity of personhood even though with different quality of power. People of Sunda Wiwitan have value of ethics and responsibility in treating nature which is heavily influenced by their world view in seeing the self, the other selves and their relation. They have a faith that between nature and Sunda Wiwitan followers cannot be separated, human beings, nature, stone, star, or even dung is microcosm while the universe itself is macrocosm. Therefore, the relation built between human and nature tends to be strong, ethical, reciprocal and responsible encounter (2) the ceremony of Seren Taun becomes an adhesive media which connects them with the ancestors -as the other-than-human persons- and God. The symbolization of tree planting in the ritual of Dadung or the performance of Buyung dance inspired by the nature and other rituals performed at the ceremony of Seren Taun has managed to provide a better understanding for people of Sunda Wiwitan in the preservation of the environment. The positive impact of Seren Taun and the rituals performed are not only applicable to the scope of Sunda Wiwitan followers, but also to those of other residents of Cigugur whose religion and faith are not Sunda Wiwitan. However, (3) there are many challenges encountered by people of Sunda Wiwitan due to the different paradigm between the traditional paradigm of Sunda Wiwitan and the development paradigm of the outsiders. One of the hot concerns is the rejection of the planning of geothermal project in Mt Ciremai Cigugur. Finally, the writer expects that this thesis will be useful for others and this study should be continued by other writers from other point of views and aspects, with more complete analysis, especially in indigenous religion and environment